Challenges of Islamic Education in Street Punk Families in Temanggung - Agustin Wulandari; Luluk Ifadah; Nur Alfi Muanayah; Ouedraogo Saidou (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2023)
This study describes a unique phenomenon that occurs in Mulyo Hamlet, Pandemulyo Village, Bulu District, Temanggung Regency. Where in Dudun Mulyo there are several families who have experiences or backgrounds that are different from parents in general, namely having experience in participating in street punk or the modern language, namely street punk. Punk itself is synonymous with violence, anarchy, resistance. Families with basic street punk tend to be less harmonious in their household. This challenge for a family with a street punk background has several factors that influence it. So there are several strategies to increase religious understanding, establish good communication between family members, have free time with family, improve the economy.